Shape coexistence studied in 182, 184Hg via the β decay of 182, 184Tl. (31st May 2017) - Rapisarda, E; Andreyev, A N; Antalic, S; Barzakh, A; Cocolios, T E; Darby, I G; Groote, R De; Witte, H De; Diriken, J; Elseviers, J; Fedorov, D; Fedosseev, V N; et al.
Abstract: The β + /EC decay of 182, 184 Tl to excited states in the daughter nuclei 182, 184 Hg has been investigated at the CERN on-line isotope mass separator facility. In both Tl nuclei two β -decaying states were observed. In the case of 184 Tl, narrow-band laser spectroscopy could be used to disentangle the decay of both isomers. In 182 Hg a precise energy of 335 (1) keV for the 0 2 + state was measured together with its feeding from a tentatively proposed 2 3 + state at 973 keV. Large conversion coefficients for the 2 2 + → 2 1 + transition in 182, 184 Hg were measured to be 7.2 (13) and 14.2 (36), respectively, evidencing a strong E0 component.